The Influence of Work-Life Balance and Organizational Culture on Job Satisfaction of Civil Servants at the UPT Puskesmas Pal 3 in Pontianak City - Wella Sari; Eru Ahmadia (SAINTIS Publishing, 2025)
This study aims to examine the influence of Work-Life Balance and Organizational Culture on Job Satisfaction among Civil Servants at UPT Puskesmas Pal 3 in Pontianak City. Utilizing a quantitative approach with an associative research design, the study employed saturated sampling, involving the entire population of 36 civil servants as respondents. The findings from the F-test demonstrate that Work-Life Balance and Organizational Culture simultaneously have a positive and significant effect on Job Satisfaction. Additionally, the t-test results reveal that both variables also exert a positive and significant individual influence, with Work-Life Balance showing a more dominant effect than Organizational Culture. The coefficient of determination (R²) value of 0.472 indicates that 47.2% of the variance in Job Satisfaction can be explained by these two independent variables, while the remaining 52.8% is attributed to other factors not included in this study. The results highlight the critical importance of promoting a healthy balance between professional and personal life, alongside fostering a constructive organizational culture, as key strategies to improve employee job satisfaction especially within the public sector. For future research, it is recommended to incorporate additional variables such as leadership style, workload, and organizational climate to achieve a more holistic understanding of the determinants of job satisfaction. Furthermore, applying a mixed-method approach and expanding the sample across multiple institutions or geographic regions may yield deeper insights and enhance the generalizability of the findings.